Kemandirian Anak Usia 5-6 Tahun dengan Pendidikan Keluarga Pada PAUD - Amin Kholiah; Susi Herlinda; Paijan Rambe (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
The purpose of this study was to analyze the independence of children aged 5-6 years through family education and to identify the supporting and inhibiting factors in the Cahaya Ibu Early Childhood Education (PAUD Cahaya Ibu). This research used a qualitative method, with data sources comprising 5 parents of children, collected through observation, interviews, and documentation, and analyzed through data reduction, presentation, and conclusions. The results of the study indicate that parents play a central role in shaping children's independence through physical, intellectual, emotional, social, and spiritual education. The supporting factor is the synergy of facilities between teachers and parents; the dominant inhibiting factor is the attitude of parents who are overly indulgent toward children, which hinders the process of their behavior maturing. The implications of this study for schools: to maintain all achievements, teachers must continue to uphold professionalism in education and strengthen synergy with parents more effectively.